Consensus Conference Statement on the General Use of Near-infrared Fluorescence Imaging and Indocyanine Green Guided Surgery: Results of a Modified Delphi Study. Issue 4 (17th April 2022) - Dip, Fernando; Boni, Luigi; Bouvet, Michael; Carus, Thomas; Diana, Michele; Falco, Jorge; Gurtner, Geoffrey C.; Ishizawa, Takeaki; Kokudo, Norihiro; Lo Menzo, Emanuele; Low, Philip S.; Masia, Jaume; et al.
Abstract : Background: In recent decades, the use of near-infrared light and fluorescence-guidance during open and laparoscopic surgery has exponentially expanded across various clinical settings. However, tremendous variability exists in how it is performed. Objective: In this first published survey of international experts on fluorescence-guided surgery, we sought to identify areas of consensus and nonconsensus across 4 areas of practice: fundamentals; patient selection/preparation; technical aspects; and effectiveness and safety. Methods: A Delphi survey was conducted among 19 international experts in fluorescence-guided surgery attending a 1-day consensus meeting in Frankfurt, Germany on September 8 th, 2019. Using mobile phones, experts were asked to anonymously vote over 2 rounds of voting, with 70% and 80% set as a priori thresholds for consensus and vote robustness, respectively. Results: Experts from 5 continents reached consensus on 41 of 44 statements, including strong consensus that near-infrared fluorescence-guided surgery is both effective and safe across a broad variety of clinical settings, including the localization of critical anatomical structures like vessels, detection of tumors and sentinel nodes, assessment of tissue perfusion and anastomotic leaks, delineation of segmented organs, and localization of parathyroid glands. Although the minimum and maximum safe effective dose of ICG were felt to be 1 to 2 mg and >10 mg, respectively, there was strong consensus that determining the optimum dose, concentration, route and timing of ICG administration should be an ongoing research focus. Conclusions: Although fluorescence imaging was almost unanimously perceived to be both effective and safe across a broad range of clinical settings, considerable further research remains necessary to optimize its use.